A new consensus on reconciling fire safety with environmental & health impacts of chemical flame retardants - Jamie Page; Paul Whaley; Michelle Bellingham; Linda S. Birnbaum; Aleksandra Cavoski; Delyth Fetherston Dilke; Ruth Garside; Stuart Harrad; Frank Kelly; Andreas Kortenkamp; Olwenn Martin; Anna Stec; et al. (Environment International, 2023)
Flame retardants are chemical substances that are intended to mitigate fire safety risks posed by a range of goods including furniture, electronics, and building insulation. There are growing concerns about their effectiveness in ensuring fire safety and the potential harms they pose to human health and the environment. In response to these concerns, on 13 June 2022, a roundtable of experts was convened by the UKRI Six Clean Air Strategic Priorities Fund programme 7. The meeting produced a Consensus Statement that summarises the issues around the use of flame retardants, laying out a series of policy recommendations that should lead to more effective fire safety measures and reduce the human and environmental health risks posed by these potentially toxic chemicals.